The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1136/emermed-2017-206625
|View full text |Cite
|
Sign up to set email alerts
|

Use of the low-frequency/high-frequency ratio of heart rate variability to predict short-term deterioration in emergency department patients with sepsis

Abstract: While we found a statistically significant relationship between HRV, SOFA and HRV+SOFA, and early deterioration, none reliably functioned as a clinical predictive tool. More complex multivariable models will likely be required to construct models with clinical utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The rationale for and feasibility of evaluating continuous HRV monitoring in the ED has been well described in previous studies[7, 22, 34]. Several studies had suggested that HRV changes may present as the earliest measurements before apparent clinical symptoms emerge [23, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for and feasibility of evaluating continuous HRV monitoring in the ED has been well described in previous studies[7, 22, 34]. Several studies had suggested that HRV changes may present as the earliest measurements before apparent clinical symptoms emerge [23, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…There are several non-invasive methods to assess heart function following sepsis including functional (Echocardiography; Echo-Doppler), electrical (electrocardiograms; ECGs) measurements and biomarkers present in the plasma. These techniques are still commonly used in septic patients in the hospital to assess cardiac function and monitor the hemodynamic condition (Barnaby, et al 2018; Beraud, et al 2014; Guerin and Vieillard-Baron 2016; Haileselassie, et al 2016; Ozdemir, et al 2016; Quinten, et al 2017; S, et al 2014; Shashikumar, et al 2017).…”
Section: Methods To Assess Heart Function In Sepsismentioning
confidence: 99%
“…Reduced RMSSD has also been shown to predict for 28-day mortality in septic patients presenting at the ED (45). Some prior studies demonstrated that a decreased LF/HF ratio of less than 1.0 may predict severity of illness in septic patients (46,47). When integrated with various components of other warning scores, HRV parameters have been found to be superior in risk-stratifying septic patients at the ED (48).…”
Section: Adult Sepsismentioning
confidence: 99%